Legal Protection for Public Shareholders Against the Implementation of Forced Delisting by the Indonesia Stock Exchange - Marihot Janpieter Hutajulu (Lembaga Pengembangan Kinerja Dosen, 2026)
Forced delisting is a form of stock delisting by the Indonesia Stock Exchange against issuers that no longer meet the requirements as listed companies. Although this policy aims to maintain the integrity and credibility of the capital market, its implementation has the potential to cause losses for public shareholders due to the loss of stock liquidity and the limited mechanisms for recovering investors' economic rights. This research aims to analyze the legal considerations and procedures of the Indonesia Stock Exchange in implementing forced delisting and to examine the effectiveness of buyback obligation regulations based on Financial Services Authority Regulation Number 3/POJK.04/2021 as a form of legal protection for investors. This research uses a normative legal research method with a statutory approach and a conceptual approach. The legal materials used include primary legal materials in the form of regulations in the capital market sector as well as secondary legal materials derived from literature, scientific journals, and relevant decisions or cases. The analysis was conducted qualitatively using a deductive method. The research results indicate that the regulation regarding the buyback obligation is a progressive step in providing an exit strategy mechanism for public shareholders after forced delisting occurs. However, the implementation of these provisions has not been fully effective because there is still a gap in the execution norms when the issuer goes bankrupt or lacks the financial capability to carry out the buyback. As a result, legal protection for investors remains normative and does not fully guaranty the recovery of the economic rights of public shareholders. Therefore, it is necessary to strengthen regulations thru clearer buyback execution mechanisms and the establishment of investor protection schemes, such as an Investor Protection Fund or escrow mechanisms, in order to achieve legal certainty, justice, and more effective legal protection in the Indonesian capital market system.